Precision public health in the making: examining the becoming of the “social” in a Swiss environmental health population-based cohort - Bühler, Nolwenn (Frontiers in Sociology, 2023)
Expanding the concept of “precision” or “personalized” medicine, personalized health and precision public health designate the use of various kinds of data—genomic, other omics, clinical, or those produced by individuals themselves through self-tracking—to optimize health interventions benefiting the whole population. This paper draws on an ethnography of the implementation of a population-based environmental health cohort to shed light on the reconfigurations brought about by the “personalization” of public health in Switzerland. Combining human biomonitoring and molecular epidemiology, this cohort aims to advance the science of the exposome, a notion referring to the totality of exposures to which individuals are subjected over their lifecourse. Addressing the tension between holism and reductionism, this paper points to the important gap between the promissory horizon of the exposome and the realities of practices. Situations of reductionism are defined as moments of friction and negotiation between different rationales and values, exposing what makes the science of the exposome, including its material, economic, institutional, and methodological constraints, as well as its imaginaries and values. Rather than opposing holism and reductionism, I emphasize that they constitute two sides of the same coin, as they both pragmatically enable action and produce situated versions of the social. This empirical case shows how reductionism operates at the chemical, biological, and populational levels to produce public health scientific and social values. It thus contributes to contextualizing the pragmatic and strategic choices made by scientists, as well as the values they favor, in a research environment marked by the predominance of biomedicine over public health. It shows how the reductionism of the “social environment” was made for a better social integration of the cohort into the Swiss political and scientific landscape of public health. Bringing together actors involved in public health and questions of environmental exposures, this cohort can be interpreted as a biomedicalization of public health research, as well as an attempt to socialize it through the broad category of the exposome.